Virtual reality does not meet expectations in a pilot study on multimodal laparoscopic surgery training - Nickel, Felix; Bintintan, Vasile V.; Gehrig, Tobias; Kenngott, Hannes Götz; Fischer, Lars; Gutt, Carsten N.; Müller, Beat P. (World journal of surgery, 2013)
The purpose of the present study was to determine the value of virtual reality (VR) training for a multimodality training program of basic laparoscopic surgery.
Gesehen am 22.11.2021